Identifikasi Miskonsepsi Video Pembelajaran Fisika Siswa Kelas X Berbasis Platform Youtube - Nurcahyono, Mochamad Rizky; Suprapto, Nadi (Universitas Negeri Surabaya, 2023)
The current pandemic period does not only have an impact on public health but also has an impact on the economic conditions, education and social life of the community. Therefore, the central and regional governments issue various policies that are preventive in the fields of economy, education and social life of the community. In world education issued a government policy of